The Roles of Organizational Culture, Participative Leadership, Employee Satisfaction & Work Motivation Towards Organizational Capabilities - Aurelia, Inezia; Musa, Soebowo (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2023)
Many firms still fail to develop organizational agility. There are more than 40% of organizations think that they are low/not agile in facing market change. Organizational culture plays an important role in developing the organizations to be adaptive in order to manage the VUCA effectively. This study examines the relationships of organizational culture towards participative leadership, employee satisfaction, employee work motivation, organizational learning, and absorptive capacity in developing organizational agility in managing VUCA environment. 263 employees located from an international chemical-based company offices across the globe, who have worked more than three years were the respondents in this study. This study showed that organizational clan culture promotes the development of participative leadership, which it has an empowering effect towards people in the organization resulting in employee satisfaction. The study also confirms the role of organizational culture in creating organizational behavior within the organization that foster the organizational learning, absorptive capacity, and organizational agility; while the study also found that the relationship between participative leadership and employee work motivation is not significant.